PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DIBEI PERIODE 2012-2016 - Rina Masithoh Haryadi, Misnah1, LCA. Robin Jonathan (EKONOMIA, 2021)
The Influence of Capital Structure on Financial Performance in Automotive Sub-Sector Companies and Components Registered on the Indonesia Stock Exchange for the period 2012-2016. This study aims to analyze the effect of Debt to Asset Ratio (DAR) on Return On Assets (ROA) on Automotive and Component Sub Sector Companies Registered on the Stock Exchange for the 2012-2016 period.. The sample selection used a purposive sampling method to obtain 11 samples of companies in the Automotive and Component Sub Sector Registered on the Indonesia Stock Exchange for the 2012-2016 period. The research data is secondary data, namely the audited financial statements and obtained through the official website of the Indonesia Stock Exchange. Based on the results of data analysis using the partial test (t-test) Debt to Asset Ratio (DAR) has a significant negative effect on Return On Assets (ROA) in the Automotive and Component Sub Sector companies listed on the IDX for the period 2012-2016 and if the DAR rises then ROA goes down. This means that the company uses more debt than capital or equity from the company as a source of corporate funding in carrying out the company's operations, so that the debt burden increases and can reduce the company's profit (Return On Assets). Based on the results of the study concluded that Debt to Asset Ratio (DAR) has a significant negative effect on Return On Equity (ROE), the hypothesisis accepted